Rethinking Libertarianism: Elizabeth Anderson's Private Government. Issue 2 (4th March 2018) - Ellerman, David
Abstract : In her recent book, Private Government, Elizabeth Anderson makes a powerful and pragmatic case against the abuses experienced by employees in conventional corporations. The purpose of this review-essay, says the author, is to contrast Anderson's pragmatic critique of many abuses in the employment relationship with a principled critique of the relationship itself. Can we really rent ourselves to our employers? This principled critique is based on the theory of inalienable rights, a theory that was the basis for the abolition of the so-called voluntary slavery in today's democratic countries. When understood in modern terms, that same theory applies as well against the voluntary "self-rental" that is the basis for our current economic system.